2009
DOI: 10.1292/jvms.001549
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Risk for Influenza A (H5N1) Infection in Wild Swan Feathers

Abstract: ABSTRACT. We examined whooper swans naturally infected with avian influenza virus (H5N1) to evaluate the possible zoonotic risk of swan feathers. Viruses were isolated from feather calami. Immunohistochemical testing revealed that virus antigens were present in the feather epidermis and feather follicle wall epidermis of some feathers. RT-PCR and genetic sequencing using paraffin sections of swan feathers confirmed the presence of avian influenza virus (H5N1) in the feather tissue. These results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…AI virus (H5N1) infection in humans in the Republic of Azerbaijan is suspected to have been caused by defeathering of infected wild swans (10). We previously reported that AI virus (H5N1) can replicate in wild swan feathers, demonstrating the zoonotic potential of feathers as a source of AI virus (H5N1) infection (55). In addition to waterfowl, histological evidence of the presence of AI virus (H5N1) in feathers has been reported for chickens experimentally infected with the virus (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI virus (H5N1) infection in humans in the Republic of Azerbaijan is suspected to have been caused by defeathering of infected wild swans (10). We previously reported that AI virus (H5N1) can replicate in wild swan feathers, demonstrating the zoonotic potential of feathers as a source of AI virus (H5N1) infection (55). In addition to waterfowl, histological evidence of the presence of AI virus (H5N1) in feathers has been reported for chickens experimentally infected with the virus (56).…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatically infected domestic ducks can shed the virus continuously from their oral cavity and cloaca, contributing significantly to silent spread of AI virus (H5N1) (15,33,38). We previously reported that AI virus (H5N1) can replicate in feather epidermal cells in ducks, geese, and swans (53,55). Feathers easily drop off the body, and infected feathers have the potential to cause environmental contamination.…”
mentioning
confidence: 99%
“…These results suggest that feathers could represent a source of environmental contamination, as well as a source of infection for other birds (including game birds or birds of prey) or mammals that pick dead individuals, and thus eat infected feathers or inhale their dusts. Furthermore, feathers may represent a risk of zoonotic infection when being plucked from dead infected birds without appropriate protective equipment, as already suggested for waterfowl (Yamamoto et al, 2009).…”
Section: Pathobiology Of Hpaivs In Minor Gallinaceous Speciesmentioning
confidence: 99%
“…Our results suggest that feathers of chickens infected with HPAI H5N1 virus could pose a risk of virus spread in the environment. Defeathering birds with suspected HPAI virus infections is not recommended unless personal protective equipment is used (19,29).…”
Section: Discussionmentioning
confidence: 99%